The Systematicity Of Interlanguage: A Case Study Of Senior High School Learning Foreign Language - Suhartini, Suhartini; , Prof. Dr. Endang Fauziati, M. Hum; , Dra. Siti Zuhriah Ariatmi, M. Hum (2013)
This study aims to describing the systematicity of written by second grade of Senior High School of MA MA'ARIF Cepogo Boyolali, describing the frequency of type systematicities, and finding the source influenced systematicity. The type of this research is descriptive qualitative research. In collecting the data, the researcher uses documentation method by selecting the systematicities which are written by second grade students. The steps for collecting the data are finding students' composition test with the topic given, reading and writing the systematicities sentences. The collected data are analyzed by using Selinker, Smith, and Saville source of systematicities theory. The results of the research show that the second grade of Senior High School of Cepogo Boyolali still make 32 systematicities in their compositions. The writer finds that from 32 data, there are present tense 16, past tense 12, and future tense 4. The highest frequency of systematicities that the researcher finds the use of V1 in past tense 86%. The researcher also finds that psychological, linguistic competence, and sociology influence the sistematicities of student's products.